2021
DOI: 10.48550/arxiv.2102.03916
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficient extended-search space full-waveform inversion with unknown source signatures

Hossein S. Aghamiry,
Frichnel W. Mamfoumbi-Ozoumet,
Ali Gholami
et al.

Abstract: Full waveform inversion (FWI) requires an accurate estimation of source signatures. Due to the coupling between the source signatures and the subsurface model, small errors in the former can translate into large errors in the latter. When direct methods are used to solve the forward problem, classical frequency-domain FWI efficiently processes multiple sources for source signature and wavefield estimations once a single Lower-Upper (LU) decomposition of the wave-equation operator has been performed. However, t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…If the location of the seismic events are known, Aghamiry et al (2021b); Fang et al (2018) have shown that it is possible to jointly estimate the data-assimilated wavefield and the event signatures with high accuracy by solving a linear least-squares problem. But, when the location and the number of seismic events are unknown, the first step of the proposed algorithm tries to find this information by applying a peak finder algorithm on the sparsified predicted source map.…”
Section: Discussionmentioning
confidence: 99%
“…If the location of the seismic events are known, Aghamiry et al (2021b); Fang et al (2018) have shown that it is possible to jointly estimate the data-assimilated wavefield and the event signatures with high accuracy by solving a linear least-squares problem. But, when the location and the number of seismic events are unknown, the first step of the proposed algorithm tries to find this information by applying a peak finder algorithm on the sparsified predicted source map.…”
Section: Discussionmentioning
confidence: 99%